Effect of Inquiry Learning Model on Students’ Motivation in History Learning at SMA Kemala Bhayangkari 01 Kubu Raya - Anggraini, Joya Reza; Firmansyah, Andang; Putri, Astrini Eka (Universitas Tanjungpura, 2025)
The project focuses on the effect of applying inquiry-based strategies in history education concerning the learning engagement levels of tenth-grade students at SMAS Kemala Bhayangkari 01 Kubu Raya. The identified problem is students' low learning motivation caused by conventional, monotonous, and less interactive teaching methods. This research utilized a quasi-experimental method to analyze the transformation in learners’ motivation before and after the inquiry model is introduced. This model emphasizes exploration, investigation, and problem-solving activities conducted independently or in groups. The results demonstrate a rise in student motivation after implementing the inquiry-based learning model, reflected in their greater involvement through asking questions, participating in discussions, and focusing on lesson content. These findings indicate that the inquiry-based learning model effectively improves students' motivation to learn history in grade X at SMAS Kemala Bhayangkari 01 Kubu Raya. This study recommends educators adopt innovative teaching strategies to address low motivation and enhance the overall quality of learning.